Respon Peserta Didik Terhadap Program Pengabdian Masyarakat Melalui Pelatihan Pengolahan Labu Kuning: Pengabdian - Febriani Lukitasari; Hidayatun Muyasyaroh; Diwyacitta Antya Putri; Nugrahani Astuti; Luthfiyah Nurlaela; Rendra Lebdoyono; Novia Tesalonika Amanda Rerung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
A  community service activity through pumpkin processing training was conducted at SMAN 1 Karas, involving 16 11th-grade students. The objectives of this activity were to provide knowledge about the nutrition and benefits of pumpkin, train food processing skills based on local ingredients, and foster student creativity in culinary product innovation. The implementation method included material delivery, creative practice, discussion, and evaluation through pre-tests, post-tests, and participant response questionnaires. The analysis results showed a significant increase in student knowledge, indicated by the difference in pre-test scores (50–60) and post-test scores (80–90). Participants' responses to the training were very positive, with average scores of 4.8–5.0 in aspects of material, instructor skills, facilities and infrastructure, and activity implementation. Participants considered the material easy to understand, the delivery method clear, and the product processing practice very useful. Several improvements were noted in aspects of instructor time discipline and the intensity of mentoring during practice. Overall, this training was effective in increasing students' knowledge, skills, and motivation to utilize local foods, especially pumpkin, as value-added product innovations. Such activities are important to continue to develop as an effort to support food diversification and entrepreneurship in the culinary field.